Hubungan Pola Makan dan Gaya Hidup dengan Kejadian Hipertensi pada Masyarakat di Desa Perkebunan Ramunia Kecamatan Pantai Labu - Nurlatipah Harahap; Regita Cahyani; Suhaila Adzhana Lubis; Nurhafiza Farhani; Priska Dwi Jayanti; Reni Agustina Harahap (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Diet is to regulate the amount and type of food in daily life. Each person's daily life eating pattern is different, so the amount and type of food that will be consumed is very important to pay attention to and regulate the system and method of food processing. Lifestyle is also the most important factor that greatly affects people's lives, because an unhealthy lifestyle can cause various diseases, one of which is hypertension. Hypertension is a disease of the cardiovascular system that causes an increase in blood pressure above normal above 140/190 mmHg. The purpose of this study was to determine the relationship between diet and lifestyle in the Ramunia Plantation village community. This cross sectional study was followed by 100 respondents by means of purposive sampling. The results of this study found the proportion of the incidence of mild hypertension was 12%, moderate was 42% and severe was 46%. Bivariate analysis using chi square test. The results of bivariate analysis showed that there was a relationship between salt consumption and hypertension (p = 0.001), salted fish consumption (p = 0.000), high fat consumption (p = 0.000), smoking habits (p = 0.306), and exercise habits (p = 0.002).